Advanced Therapy Medicinal Products and Exemptions to the Regulation 1394/2007: How Confident Can We be? An Exploratory Analysis - Van Wilder, Philippe (Frontiers in Pharmacology, 2012)
The market authorization procedure for medicinal products for human use is relying on their demonstrated efficacy, safety, and pharmaceutical quality. This applies to all medicinal products whether of chemical or biological origin. Since October 2009, the first advanced therapy medicinal product (ATMP) has been authorized through the centralized procedure. ATMPs are gene therapy medicinal products, somatic cell therapy medicinal products or tissue-engineered products. An appropriate ATMP – Regulation is dealing with ATMP requirements. Two exemptions are foreseen to the ATMP Regulation: (a) Products, which were legally on the Community market when the Regulation became applicable, should comply to the Regulation by December 30, 2012. (b) The hospital exemption rule for non-routine products for an individual patient. In this work we explored whether the actual application of the Regulation on ATMPs is in line with the aim of the Regulation in terms of guaranteeing the highest level of health protection for patients. Based on the analysis of the relative efficacy of the only EC authorized ATMP and its exempted alternatives, there is evidence against this Regulation 1394/2007 assumption.